A single‐phase, thermally stable and color-tunable white light emitting Na2Ca1-x-yCexMnyP2O7 phosphors for white light emitting diodes via energy transfer. Issue 10 (15th May 2023) - Meena, Mohan Lal; Som, Sudipta; Chaurasiya, Rajneesh; Lin, Shawn D.; Lu, Chung-Hsin
Abstract: The solid-state reaction method was used to develop a series of Na2 Ca1-x-y Cex Mny P2 O7 phosphors in an H2 –N2 environment. The crystal structure of the pyrophosphate host, valence state of dopants (Ce, Mn), emission behavior of dopants, energy transfer mechanism, and thermal quenching behavior were thoroughly examined. Doping with Ce 3+ and Mn 2+ ions enhanced the photoluminescence characteristics of Na2 Ca1-x-y Cex Mny P2 O7 while having negligible effect on the host's phase purity. Under 365 nm UV light irradiation, the addition of Ce 3+ ion in the Na2 CaP2 O7 host revealed an asymmetric band with the typical blue emission around 415 nm and a shoulder around 455 nm. To obtain white light, Mn 2+ ion was supplementarily substituted to the present system. When the Mn 2+ ions concentration was elevated in the Na2 CaP2 O7 host, the emission intensity of 560 nm peak corresponding to Mn 2+ transition enhanced significantly at the cost of Ce 3+ emission of 415 nm. The systematic decrease of Ce 3+ emission intensity and corresponding increase in the Mn 2+ intensity with the increase in Mn 2+ concentration indicated the possibility of effective energy transfer from Ce 3+ to Mn 2+ ions. The obtained results indicated that energy transfer from the Ce 3+ to Mn 2+ ions governed by dipole-quadrupole interaction. Because of the efficient energy transfer, the blue emission from Ce 3+ and the orange red emission of Mn 2+ provide white light from a single host along with high value of activation energy and low thermal quenching behaviour make the present phosphors to be suitable for high-power LEDs.